Efektivitas Mediasi dalam Penyelesaian Sengketa Perkawinan, Guna Pemenuhan Hak Hak Istri Pasca Perceraian (Nafkah Iddah): Studi Kasus di Pengadilan Agama Rangkasbitung - Heni Rohaeni (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2023)
The Mediation process can be an effective instrument in ensuring the fulfillment of womens rights/Iddah rights for women after divorce at the Rangkasbitung Religious Court, by exploring divorce cases involving Mediation, with a focus on how Mediation accommodates iddah rights, the obstacles faced and the factors that influence its success, research results It is hoped that this will provide a deeper understanding of the role of mediation in protecting women's rights, especially in the context of divorce in Indonesia and provide recommendations for improving mediation policies and practices.